Impact of 30° Reserve Trendelenburg Position on Lung Function in Morbidly Obese Patients Undergoing Laparoscopic Sleeve Gastrectomy - Gao, Dengyu; Sun, Lu; Wang, Ning; Shi, Yubo; Song, Jianli; Liu, Xiaoying; Yang, Qiyao; Su, Zhenbo (Frontiers in Surgery, 2022)
Background The aim of this study was to evaluate the impact of patient’s positioning before and after intubation with mechanical ventilation as well as after extubation on morbidly obese patients’ lung function and blood oxygenation, who had laparoscopic sleeve gastrectomy. Methods Morbidly obese patients (BMI ≥ 30 kg/m2, ASA I - II grade), who underwent laparoscopic sleeve gastrectomy at our hospital from June 2018 to January 2019, were enrolled into this prospective study. Before intubation, after intubation with mechanical ventilation, and after extubation, arterial blood was collected for blood oxygenation and gas analysis after posturing the patients at supine position or 30° reverse Trendelenburg position (30°-RTP). Results Total 15 morbidly obese patients were enrolled into this self-compared study. Pulmonary shunt (Qs/Qt) after extubation was significantly lower at 30°-RTP (18.82 ± 3.60 %) compared to that at supine position (17.13 ± 3.10 %, P < 0.01); patients’ static lung compliance (Cstat) during mechanical ventilation was significantly improved at 30°-RTP (36.8 ± 6.7) compared to that at supine position (33.8 ± 7.3, P < 0.05); PaO2 and oxygen index (OI) before and after intubation with mechanical ventilation were significantly higher at 30°-RTP compared to that at supine position; and in contrast, the PA-aO2 before and after intubation with mechanical ventilation was significantly reduced at 30°-RTP compared to that at supine position. Conclusion During and after laparoscopic sleeve gastrectomy, morbidly obese patients had improved lung function, reduced pulmonary shunt, reduced PA-aO2 difference, and increased PaO2 and oxygen index at 30°-RTP compared to that at supine position.